Strengthening Workplace Well-Being in Research Animal Facilities - Murray, Judy; Bauer, Cassondra; Vilminot, Nicole; Turner, Patricia V. (Frontiers in Veterinary Science, 2020)
In recent years, there has been an increased recognition of the potential cost of caring on the mental well-being of research animal facility personnel. While this issue is considered a normal consequence of caring for others, these stressors must be acknowledged and managed to ensure that the workplace culture remains positive and that employees are engaged. Factors that can contribute to these feelings in those working with animals in research include compassion and moral stress, issues related to staffing and scheduling of work, insufficient communication in the workplace, and public ambivalence towards the use of animals in science. The first step in developing a program is to survey facility personnel about their concerns, either formally (e.g., using a needs analysis) or informally. Two examples are provided to demonstrate different institutional approaches to assessing personnel needs and developing an internal compassion-resiliency program. The best programs are based on the needs and wants of personnel and these can be cost effective and geared at a grassroots level. Social support in the workplace, for example, through peer counselling, can be a highly effective means of helping personnel to build compassion-resiliency. Addressing mental well-being of research animal facility personnel is an important component of ensuring a positive culture of care in the workplace.